2001
DOI: 10.1177/109019810102800307
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Practice of Health Promotion Initiatives by Licensed Premises

Abstract: Licensees of all licensed premises in the Hunter Region of New South Wales, Australia, were offered free services to encourage adoption of health promotion initiatives relating to responsible service of alcohol, environmental tobacco smoke, healthy food choices, breast and cervical cancer prevention, and the prevention of HIV/AIDS. A total of 239 premises participated in the follow-up survey. Increases in prevalence ranged between 11% and 59% for alcohol-related initiatives. The prevalence of smoke-free areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…The prevalence estimates of responsible hospitality policies reported in this study are very similar to those reported previously from the study region [19]. Previously, almost 100% of premises in the study area have been reported as having responsible service policies, training their staff in the responsible service of alcohol, and promoting safe transport options.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence estimates of responsible hospitality policies reported in this study are very similar to those reported previously from the study region [19]. Previously, almost 100% of premises in the study area have been reported as having responsible service policies, training their staff in the responsible service of alcohol, and promoting safe transport options.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that the prevalence of responsible hospitality policies may be higher in the study region, given the recent occurrence of other harm reduction initiatives [19]. First, the study used a non-random sample of licensed premises associated with alcoholrelated harm.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study relied on the self-report of club delegates to report on club alcohol management practices. While the validity of such self-reported assessments are not known, self-reported assessment of the health promotion policies and practices of alcohol outlets as well as community organisations such as schools and childcare services is common [55-57], with representatives of such organisations having previously been found to validly and reliably report organisational policies and practices [58,59]. …”
Section: Resultsmentioning
confidence: 99%
“…Second, the presence of alcohol management practices in clubs was based on the self‐report of club practices, and hence may be an over estimate of the actual prevalence of such practices. Although studies of the validity of such self‐report has been reported, previous studies conducted in licensed premises have reported acceptable validity for licensee reporting of alcohol management practices 53 …”
Section: Discussionmentioning
confidence: 99%